The historical antecedents of the Free School Act and the Public School Act of PEI - McGuigan, Derrill Ignatius (University of Ottawa (Canada), 1924)
Abstract not available.
Keywords: History, Canadian.; Education, Administration.; Education, History of.; Political Science, Public Administration.